Social policy review. edited by Ian Greener, Chris Holden, Majella Kilkey. - Greener, Ian; Holden, Chris; Kilkey, Majella (Social policy series ;, 2010)
Essential reading for academics and students in the field, Social Policy Review 22: Analysis and Debate in Social Policy, 2010 presents an up-to-date and diverse review of the best in social policy scholarship, including an assessment of Labour's social policy after three terms in office.